Health service utilization and associated factors among fee waiver beneficiaries in Ethiopia: Systematic review and meta-analysis - Bizunesh Fantahun Kase; Hiwot Altaye Asebe; Etsay Woldu Anbesu; Dejen Kahsay Asgedom; Abubeker Alebachew Seid; Abdulkerim Hassen Moloro; Aragaw Asfaw Hasen; Nuru Mohammed Hussen; Molla Getie Mehari; Kassaye Getaneh Arge; Abdu Hailu Shibeshi (PLoS ONE, 2025)
Background Health service utilization serves as a vital indicator of healthcare access and equity. In Ethiopia, the fee waiver system is a key component of healthcare financing reforms designed to improve access to essential health services for economically disadvantaged populations. However, the evidence regarding health service utilization among fee waiver beneficiaries remains inconsistent. This systematic review and meta-analysis synthesize existing studies to provide comprehensive insight on health service utilization and associated factors among fee waiver beneficiaries in Ethiopia. Methods A systematic search of peer-reviewed articles and gray literature was conducted up to February 2024, in databases such as PubMed/MEDLINE, African Journals Online (AJOL), Cumulative Index to Nursing & Allied Health Literature (CINAHL), Science Direct, Research4life, and Google Scholar. A systematic review and meta-analysis were conducted in accordance with the PRISMA guidelines. Data were extracted using Microsoft Excel and analyzed with STATA 17 software. The quality of studies was assessed using Joanna Briggs Institute (JBI) checklists. The pooled prevalence of health service utilization among fee waiver beneficiaries was estimated using random-effects meta-analysis. Subgroup analyses were performed based on study regions. Publication bias was evaluated with a DOI plot, the Luis Furuya Kanamori (LFK) index, and Egger’s test, while heterogeneity was assessed using the I² statistic. Results The study analyzed seven primary studies comprising a total of 11,488 participants. All the included studies demonstrated a low risk of bias, and no significant evidence of publication bias was detected among them. The pooled prevalence of health service utilization was found to be 60.57% (95% CI: 58.11–63.04; I² = 54.2%, p = 0.041). A family size of fewer than five was negatively and significantly associated with health service utilization (OR = 0.69, 95% CI: 0.51–0.95; I² = 0.0%, p = 0.47). On the other hand, having chronic diseases was positively and significantly associated with health service utilization among fee waiver beneficiaries (OR = 4.85, 95% CI: 1.34–17.56; I² = 93.5%, p < 0.001). Residence showed no significant association (OR = 1.58; 95% CI: 0.03–71.49), with wide confidence intervals reflecting considerable uncertainty. Conclusion The findings suggest that a significant number of beneficiaries accessed health services, indicating that the system is likely contributing to enhanced healthcare access for the target population. However, this also highlights the need for further efforts to ensure broader and more equitable utilization. The analysis reveals that health service utilization is negatively associated with a family size of fewer than five and positively associated with having chronic diseases. To improve the utilization rate among poor populations, policymakers in Ethiopia should implement integrated strategies that address these key factors and target barriers to healthcare access.